Blood of the south - Clare, Alys (Clare, Alys. Aelf Fen Norman series., 2014)
In Autumn of 1093, Lassair encounters a veiled noblewoman on the quay at Cambridge, set on by an angry mob. She has no idea that the woman, alone but for her infant child, brings both mystery and peril. Then a devastating flood hits the fens, and among the wreckage washed up Aelf Fen is a body. Lassair, in the company of a sheriff's officer, wonders if she is dealing with murder. Meanwhile, in the south, Lassair's beloved Rollo is moving with relief towards the conclusion of his mission for King William in the Holy Land. But then disaster strikes, and, with the mighty forces of an emperor on his heels, abruptly he turns from hunter to hunted. In order to escape alive, he risks help from a stranger, and embarks on a voyage that turns out to be far more dangerous than he could ever have imagined.